Derivation of Identities Involving Bernoulli and Euler Numbers - Imju Lee; Dae San Kim (International Journal of Mathematics and Mathematical Sciences)
We derive some new and interesting identities involving Bernoulli and Euler numbers by using some polynomial identities and p-adic integrals on ℤ𝑝.